Flexural strengthening of RC continuous slab strips using NSM CFRP laminates - Dalfré, Gláucia (2011)
To assess the effectiveness of the near surface mounted (NSM) technique, in terms of load carrying and moment redistribution capacities, for the flexural strengthening of continuous reinforced concrete (RC) slabs, an experimental program was carried out. The experimental program is composed of three series of three slab strips of two equal span length, in order to verify the possibility of increasing the negative (at the intermediate support region) resisting bending moment in 25% and 50% and maintaining moment redistribution levels of 15%, 30% and 45%. Though the flexural resistance of the NSM strengthened sections has exceeded the target values, the moment redistribution was relatively low, and the increase of the load carrying capacity of the strengthened slabs did not exceed 25%. This experimental program is analyzed to highlight the possibilities of NSM technique for statically indeterminate RC slabs in terms of flexural strengthening effectiveness, moment redistribution and ductility performance. Using a FEM-based computer program, which predictive performance was appraised using the obtained experimental results, a high effective NSM flexural strengthening strategy is proposed, capable of enhancing the slab’s load carrying capacity and maintaining high levels of ductility.